Infertility management in resistant ovary syndrome: a review - Yi, Hong; Chen, Lin; Zhang, Jinglei; Wen, Yangxing; Zheng, Xi; Chen, Xiaoyan (Frontiers in Endocrinology, 2025)
Resistant ovary syndrome is a rare endocrinological disorder characterized by elevated serum gonadotropins and normal ovarian reserves. The leading causes of this condition include FSHR mutations, and autoimmune disorders. Due to follicle maturation defects and anovulation, these patients have menstrual disturbances and infertility. Endocrinological disorders can be treated by regular hormone replacement therapy. However, there is no consensus regarding the infertility issues and current treatment remains experimental with controlled ovarian stimulation (COS) and in vitro maturation. Herein, we conducted a review of the current literature, which concludes that: 1) patients with FSHR mutations had very poor COS outcomes; 2) follicle-stimulating hormone and luteinizing hormone levels poorly predict COS outcomes; 3) both recombinant and urinary gonadotropins may be effective in COS; 4) the dosage of exogenous gonadotropins is not the key to successful COS; 5) in vitro maturation is a feasible option for patients carrying FSHR mutations or unsuccessful COS cycles.